The relationship between self-efficacy and academic motivation among students of medical sciences - Gh. Roohi; H. Asayesh; S. A. Bathai; A. R. Shouri Bidgoli; M. T. Badeleh; H. Rahmani (Journal of Medical Education and Development, 2013)
Introduction: self-efficacy is referred to individual's beliefs about their abilities to learn and doing significant tasks in life. This study aims to determine the relationship between self-efficacy and academic motivation in a group of medical sciences' students. Methods: In this cross-sectional study 275 students of Golestan University of Medical Sciences (GOUMS) were selected using stratified random sampling method. A questionnaire consists of questions regarding demographic, academic motivation, and self-efficacy beliefs were used to collect data. Pearson correlation coefficients, independent T-Test and one way ANOVA were applied on the data. Results: The average of students’ academic motivation was 30.3±4.0. 50.2 percent of students had self-efficacy higher than average. Self-efficacy had significant correlation with intrinsic motivation sub-scale (r=0.196, P=0.001) and total score of academic motivation scale (r=0.155, P=0.01). There were no significant correlations between self-efficacy and extrinsic motivation (r=0.054, P=0.376) and motivation sub-scale (r=0.104, P=0.08). There was no significant difference between two genders in self-efficacy. Conclusion: Improvement in self-efficacy of medical sciences' students could improve their motivation.